Marine Chitinolytic Pseudoalteromonas Represents an Untapped Reservoir of Bioactive Potential - Sara Skøtt Paulsen (American Society for Microbiology, 2019)
ABSTRACT Chitin is the most abundant polymer in the marine environment and a nutrient-rich surface for adhering marine bacteria. We have previously shown that chitin can induce the production of antibiotic compounds in Vibrionaceae, suggesting that the discovery of novel bioactive molecules from bacteria can be facilitated by mimicking their natural habitat. The purpose of this study was to determine the glycosyl hydrolase (GH) profiles of strains of the genus Pseudoalteromonas to enable selection of presumed growth substrates and explore possible links to secondary metabolism. Genomic analyses were conducted on 62 pigmented and 95 nonpigmented strains. Analysis of the total GH profiles and multidimensional scaling suggested that the degradation of chitin is a significant trait of pigmented strains, whereas nonpigmented strains seem to be driven toward the degradation of alga-derived carbohydrates. The genomes of all pigmented strains and 40 nonpigmented strains encoded at least one conserved chitin degradation cluster, and chitinolytic activity was phenotypically confirmed. Additionally, the genomes of all pigmented and a few nonpigmented strains encoded chitinases of the rare GH family 19. Pigmented strains devote up to 15% of their genome to secondary metabolism, while for nonpigmented species it was 3% at most. Thus, pigmented Pseudoalteromonas strains have a bioactive potential similar to that of well-known antibiotic producers of the Actinobacteria phylum. Growth on chitin did not measurably enhance the antibacterial activity of the strains; however, we demonstrated a remarkable co-occurrence of chitin degradation and the potential for secondary metabolite production in pigmented Pseudoalteromonas strains. This indicates that chitin and its colonizers of the Pseudoalteromonas genus represent a so far underexplored niche for novel enzymes and bioactive compounds. IMPORTANCE Infectious bacteria are developing and spreading resistance to conventional treatments at a rapid pace. To provide novel potent antimicrobials, we must develop new bioprospecting strategies. Here, we combined in silico and phenotypic approaches to explore the bioactive potential of the marine bacterial genus Pseudoalteromonas. We found that pigmented strains in particular represent an untapped resource of secondary metabolites and that they also harbor an elaborate chitinolytic machinery. Furthermore, our analysis showed that chitin is likely a preferred substrate for pigmented species, in contrast to nonpigmented species. Potentially, chitin could facilitate the production of new secondary metabolites in pigmented Pseudoalteromonas strains.